2020
DOI: 10.1103/physreve.102.063105
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing most irregular small-scale structures in turbulence using local Hölder exponents

Abstract: Two scalar fields characterizing respectively pseudo-Holder exponents and local energy transfers are used to capture the topology and the dynamics of the velocity fields in areas of lesser regularity.The present analysis is conducted using velocity fields from two Direct Numerical Simulations (DNS) of the Navier-Stokes equations in a triply periodic domain. A "typical irregular structure" is obtained by averaging over 213 most irregular events. Such structure is similar to a Burgers vortex, with non-axisymmetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Yet, there are still a few places where h is below 1 (see Figure 4b), so that the field is non-differentiable. The same procedure has been repeated for velocity fields in the inertial range, resulting in values of h even smaller than h = 1/3, see [44]. The probability distribution function for h that one can get from such plots (Figure 4b) coincides by construction with (∆x) C(h) .…”
Section: Connection With Multi-fractal Formalism and Construction Of ...mentioning
confidence: 92%
See 2 more Smart Citations
“…Yet, there are still a few places where h is below 1 (see Figure 4b), so that the field is non-differentiable. The same procedure has been repeated for velocity fields in the inertial range, resulting in values of h even smaller than h = 1/3, see [44]. The probability distribution function for h that one can get from such plots (Figure 4b) coincides by construction with (∆x) C(h) .…”
Section: Connection With Multi-fractal Formalism and Construction Of ...mentioning
confidence: 92%
“…The most irregular structures of a given data set can be obtained by looking for places where the pseudo-Holder exponent takes its lowest value, and then analyzing the features of velocity and vorticity field around that place. This was done in [44] for DNS. In Figure 4d, we report a plot of the vorticity field in the experimental case.…”
Section: Observation Of Most Irregular Structurementioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the 'spottiness' of the flow and the coexistence of regions of high and low enstrophy can clearly be seen in figure 1(f), which shows the regions of most intense vorticity in the flow. In particular, it would be interesting to connect these aspects with recent results quantifying this intermittency in terms of multifractality [78][79][80][81].…”
Section: Discussionmentioning
confidence: 99%
“…Previous experimental [ 30 , 31 ] and numerical investigations [ 32 ] about the location of the structures with extreme local energy transfer showed that they are located near interactions (possibly reconnection) of Burgers vortices. Previous and recent high-resolution numerical simulations of reconnection of anti-parallel vorticity filaments [ 33 , 34 ] showed that the process is associated with the formation of a local cusp over each filament that could possibly lead to a singular behaviour [ 35 ].…”
Section: Dynamics Of a Pair Of Pinçonsmentioning
confidence: 99%